Sexual communication between parents-adolescents during covid-19 pandemic in Malang - Maimunah, Siti; Afiatin, Tina; Febriani, Arum (University of Muhammadiyah Malang, 2023)
Implementing sexual communication between parents-adolescent is essential to protect adolescents’ sexual health. This research seeks to determine how parents-adolescents’ sexual communication was implemented during the COVID-19 pandemic. This research utilised a descriptive quantitative research method. One hundred sixty-seven parents participated in this study and were recruited through links that WhatsApp and Facebook shared. The parents must have adolescents between 11-19 years old and unmarried. The result revealed that the communication between parents and adolescents was more intense during the pandemic. Moreover, 16% of the time dedicated to it was increased. However, only a small number of parents (11.4%) recorded conducting sexual communication with their teenagers. 88% of respondents reported that the duration their teens spent online had increased, even though 55.6% of them implemented a limit on their internet time. The t-test independent sample result revealed communication differences assessed from gender (0.019) and age (0.025). However, there were no differences in education (0.081) and residential area (0.663). The expectation of this study’s outcome could be expected as a reference for the related government institutions and private organisations to enact an intervention program for parents about the importance of sexual communication for adolescents’ physical and mental health.